Jawaharlal Nehru rebel and statesman - Nanda, B. R. (Bal Ram) 1917- (Oxford University Press, 1998)
Full of fascinating and rare halftones of Nehru, this biography strikes a much-needed balance between the adulation accorded Nehru during his lifetime and the denigration - often quite ill-founded - heaped upon since.